Outcomes of Geriatric Hip Fractures Treated with AFFIXUS Hip Fracture Nail - Ahmed Mabrouk; Mysore Madhusudan; Mohammed Waseem; Steven Kershaw; Jochen Fischer (Advances in Orthopedics)
Geriatric hip fractures are one of the commonest fractures worldwide. The purpose of this study was to report the outcomes of a series of unstable geriatric hip fractures treated with AFFIXUS hip fracture nail. A retrospective study of 100 unstable geriatric hip fractures treated with AFFIXUS hip fracture nail is presented. The mean follow-up duration was 8 months (range 3–32). Of the patients 83% were female. The average age was 85 years. The fracture was treated by closed reduction and intramedullary fixation. The mean acute hospital stay was 17.6 days. Systemic complications occurred in 29 patients (29%) and local complications in 3 patients (3%) including lag screw cutout in one patient (1%), lag screw backout in one patient (1%), and deep infection in one patient (1%). Mechanical failures and periprosthetic fractures were not observed in our series. Fractures united in all patients. Preinjury activity level was recovered in 78% of the patients. The results of AFFIXUS hip fracture nail were satisfactory in most elderly patients. The unique design of the lag screw and its thread spacing had effectively reduced cut-out rate.